New literacies for teachers: researching the curriculum design, materials development, implementation and redesign of a compulsory, core course in literacy for first year B Ed students - Reid, Jean Mary (My University, 2016)
This research explores the processes involved in designing and developing a compulsory course, New Literacies for Teachers, for first year Bachelor of Education (B.Ed.) students at the Wits School of Education (WSoE). The need for academic literacy development has long been recognised in various ways in programme development at most universities around the world. This course takes a broader perspective on literacy and aims to develop students as fully literate subjects. The conceptualisation of the course is based on a sociocultural approach which sees literacy as a set of socially situated practices. The course development team began by identifying five literacy domains that are important for student teachers: academic literacies, research literacies, personal literacies, school literacies and multimodal and digital literacies. Initial curriculum design developed a course structure that would enable the course designers to pull these literacy domains through the curriculum as threads for the year, thus implementing socio-cultural theory in practice. The main research question is “What processes enabled and/or constrained the design, implementation and redesign of a New Literacies for Teachers course for first year B.Ed. students?” The sub questions specifically identify the processes of curriculum design, interdisciplinary design and group collaboration. The data consists of tape recordings and transcriptions of all the course meetings during the processes of curriculum design, materials development (2009), implementation and redesign (2010). This data was analysed in two ways. The processes of curriculum design, interdisciplinary design, implementation and redesign were analysed using thematic content analysis. The process of group collaboration was analysed using a sociolinguistic approach that focussed on the dynamics of the groups and a discourse analysis of patterns of interaction. The findings provide insight into the course design and redesign processes, selection of content, framing, sequencing, pacing, the conditions of implementation and the dynamics that affected group participation and interaction. During implementation several problems emerged: logistical constraints, curriculum overload, lack of systematic development of academic literacy, problems with interdisciplinary design and lack of systematic assessment and constructive alignment (Biggs, 2003). These problems were addressed in the redesign. Whilst a key purpose of the course was to design an “integrated curriculum” (Bernstein, 1996, 2000) in which students could apply what they had learned in New Literacies for Teachers to their own studies and in their own teaching, the initial attempt at interdisciplinary design in the first semester proved to be quite difficult to achieve. One of the main findings in the analysis is that knowledge about socio-cultural theories are the privileged funds of knowledge in this course, and the lack of these funds of knowledge on the part of course designers from other disciplines and tutors on the course proved to be critical. Although the initial attempts at interdisciplinary design were a failure, the course designers found an alternative way of working with literacy across the curriculum in the second semester that introduced students to the way literacy works in the subjects they were preparing to teach. The conclusion summarises the findings about literacies for teachers; curriculum design and development; and group collaboration. Key words: socio-cultural theory of literacy, literacy domains, literacy practices, literacy across the curriculum, curriculum design, materials development, implementation, redesign, group dynamics, group interactions, teacher education
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements of the degree of Doctor of Philosophy Johannesburg, 2016
Keywords: Education -- Curricula.; Education, Higher -- Curricula.